Knowledge and Attitude toward Organ Donation and Transplantation among the Adult Population in Bisha, Saudi Arabia - Abdullah H. Alhalafi; Abdullah M. Alkhushayl; Nawaf M. Altayyib; Partha A. Nandi; Elhadi Miskeen (Journal of Pharmacy and Bioallied Sciences)
Background: This study aims to raise awareness and perceptions regarding organ donation among adults in Bisha, Saudi Arabia. Methods: An analytical cross-sectional study was conducted from May 2021 to April 2022 using a well-structured questionnaire distributed via media. Sociodemographic data and awareness of organ donation were evaluated. Results: Out of 417 respondents, 65.7% had average to good knowledge, and 69.8% had a positive attitude toward organ donation. Mass media was the primary information source (29%). Willingness to donate was motivated by saving lives (71.7%), while fear of health complications deterred others (56.6%). Conclusions: Improving knowledge and attitudes is crucial to addressing organ donation shortages.